Female representation in Singapore's publicly listed companies - Cheong, Tricia Shi Min (2017)
This study aims to provide an in-depth understanding of the female role model effect on female board directorship and the relationship between female directors and firm’s performance, in the context of Singapore. An analysis is conducted based on two events: the appointment of Ms Ho Ching as the Chief Executive Officer of Temasek Holdings in 2004, and the formation of Singapore government’s Diversity Action Committee in 2013. The results indicate that Ms Ho Ching’s appointment results in a differential increase in female board membership in government linked corporations, relative to non-government linked corporations listed in Singapore. In addition, the proportion of female directors has a positive influence on firm outcomes but not policy decisions.